Emotional labor & COVID-19: MPA program director perspectives. (3rd July 2022) - Rinfret, Sara R.; McCandless, Sean; Grewell, Cara
ABSTRACT: Emotional labor refers to the management and regulation of emotions as part of one's professional role. This research is one of the first to provide insight into the role of emotional labor during a global pandemic for Master of Public Administration (MPA) Program directors. Our paper both replicates and extends previous work in emotional labor through examining survey data from 92 MPA Directors. Using emotional labor as our descriptive framework, the findings suggest gender and academic rank indicate whose workload has been affected during the coronavirus pandemic. Furthermore, the results indicate the likelihood of greater burdens experienced by women, both white women and women of color. Our findings offer additional understanding about how emotional labor continues to impact certain populations within our public administration and policy discipline, sounding the alarm for MPA programs to address the problems at hand.